Akumulasi Timbal dalam Cakar Ayam Kampung - -, Djohan; Rangga Tabbu, Charles (Jurnal Veteriner, 2010)
Domestic chickens tend to consume lead (Pb) from their contaminated environment especially in freerangingchickens. Feet of domestic chickens are commonly consumed by many people, making them goodbioindicator to be analyzed for environmental monitoring and food safety purposes. Accumulation of leadin feet and parts of feet (tarsometatarsus bones, digiti, and skin-muscles) were investigated in this study.The average concentrations of lead in whole feet, tarsometatarsal bones, digiti, and skin-muscles were 3.4,3.8, 3.3, and 1.9 ?g.g-1 d.m., respectively. The average amount of Pb accumulated in chicken feet ranges from25.5 to 74.7 ?g. Consumption of 0.5 – 2 chicken feet. A day-1 (low – high intake) results in the exposure of 4,8to 111,5 ?g. individual-1.day-1, which was much higher than the daily exposure standar of 1 ?g. individual-1. day-1. However, very low intake (< 0.1 chicken feet.day-1) results in exposure lower than the recommendedexposure standard. More frequent monitoring and exposure assessment combined with the awareness ofgeneral public on lead contamination in the environment are important for minimizing the risk of leadexposure to human through chicken feet consumption.
Keywords: domestic chicken, chicken feet, lead, accumulation, exposure asessment.